Peat mosses (Sphagnaceae) in mires of the Sudetes Mountains (SW Poland) : a floristic and ecological study - Wojtuń, Bronisław (Wydawnictwo Akademii Rolniczej we Wrocławiu, 2006)
This investigation presents the results of studies on Sphagnum species di-versity and ecology in mires of the Polish part of the Sudetes Mountain region. The treatment comprises floristic and ecological parts: the former is based on a survey of Sphagnum species in 51 mountain mires, whereas the latter is based on detailed ecologi-cal study of 141 stands.
Keywords: torfowce; torfowiska; Sudety